Adenoid type of basal cell carcinoma: Rare histopathological variant at an unusual location - Swagata A Tambe; Smita S Ghate; Hemangi R Jerajani (Wolters Kluwer Medknow Publications, 2013)
Basal Cell Carcinoma (BCC) is almost exclusively seen in head-neck region with rare involvement of trunk and extremities. The tumour is commonly seen on nose, eyelids, at the inner canthus of eyes and behind the ears. Adenoid type of BCC is one of the rare histopathological types of BCC which has not found to have any site predilection. We report two cases of BCC occurring at an unusual site i.e., lower back and both of them showed adenoid type of BCC on histopathology. Morphologically they were pigmented and ulcerative type of BCC respectively.